PSYCHOLOGICAL STUDIES OF CREATIVITY IN WRITING - Basri, Nurfajriah; Nur, Sahril; Salija, Kisman; Nur, Safar (Universitas Muhammadiyah Makassar, 2022)
This paper is a critical literature review of psychological studies of creativity in writing from the top studies year 2013 until 2022 and compares crucial criteria and techniques. This systematic review attempts to address three research questions, i.e What is the research theory of existing studies that are being investigated based on a systematic literature review, what psychological aspects of creative writing are discussed in the reviewed paper, and what research methods were used in the studies that were included. Eight studies systematically reviewed all aspects of psychology from these studies, the findings of this study also mostly measured students’ motivation in creating writing from various education levels. Mostly, the previous researcher used a quantitative method to analyze the data that were 4 articles in the reviewed paper. Meanwhile, a similar number of articles were qualitative and quantitative methods. Keywords: Psychological studies, Creativity in writing, systematic review